Effect Of Different Size Of Banana Fibers On The Mechanical And Thermal Properties Of Banana Fiber Filled Agar Fiberboard - Teh, Ye Sam (Universiti Sains Malaysia, 2017)
Banana tree stem fiber and commercialized agar are used to produce banana fiber/agar fiberboard using compression moulding process. The effect of fiber size on the mechanical properties of the fiberboard and thermal stability of the composite as compared to both the banana fiber and agar are investigated. Fiber size of each sample, labelled as Size A, Size B and Size C respectively, are controlled by using sieve of different mesh size in a grinding process. The fiber used in Size A fiberboard is grinded and sieved by using 100 mesh size sieve, Size B 20 mesh size sieve and Size C 6 mesh size sieve. The samples formed are cut according to ASTM and their mechanical properties are obtained using tensile test, flexural test and impact test are tested. Agar powder, banana fiber and banana fiber/agar fiberboard are then used respectively for thermogravimetry analysis (TGA) test in order to obtain their thermal properties. In the test, it is shown that the tensile strength of fiberboard specimens of Size A (sieved by sieve of 100 mesh) possess the lowest tensile strength of 11.20 MPa, followed by the Size C fiberboard specimen (sieved by sieve of 20 mesh) of 13.62 MPa and Size B fiberboard specimen (sieved by sieve of 6 mesh) of 14.49 MPa. In the flexural test, the flexural strength of the Size B fiberboard specimen is the highest, which is 35.04 MPa, followed by the Size A, 26.13 MPa and the Size C fibreboard, 35.04 MPa. In the impact test, it is shown that the impact strength of the Size C fiberboard possess the highest impact strength at 15.88 kJ/m2, followed by that of Size B fiberboard specimen, 13.28 kJ/m2 and that of Size A fiberboard specimen at 9.659 kJ/m2. TGA test has shown that the banana fiber/agar fiberboard has a lower thermal stability compared to pure banana fiber as well as pure agar sample.